The Role of von Willebrand Factor in Pre-Eclampsia - Bergmann, Frauke; Rotmensch, Siegfried; Rosenzweig, Bruce; How, Helen; Chediak, Juan (Thrombosis and Haemostasis, 1991)
The von Willebrand factor (vWF) has gained considerable interest in recent years as a marker of endothelial cell activation or insult and by virtue of its interactions with platelets and vessel walls. Altered patterns of vWF multimers were found to occur frequently in patients with thrombotic thrombocytopenic purpura in the acute and chronic stages. This disorder shares some clinical and laboratory findings with pre-eclampsia, including thrombocytopenia. Recent studies have also suggested that abnormalities of endothelial cell metabolism play a central role in the pathophysiology of pre-eclampsia. In order to determine if vWF could be instrumental in the disease process and the thrombocytopenia of pre-eclampsia we analyzed the ante- and postpartum structural and functional distribution of vWF. This data was correlated with hematological parameters such as platelet counts and the clinical severity of the disease. We found no consistent changes of vWF in association with thrombocytopenia or clinical severity. However, functional vWF was lower in postpartum samples of severely affected pre-eclamptics as compared to normal controls. This finding may reflect endothelial cell exhaustion after stimulation or cellular injury. Elevated titers of fibrin split products and thrombocytopenia were evident in severe pre-eclampsia, as seen in DIC, despite factor VIII coagulant levels within the normal range. Our data is consistent with the hypothesis of endothelial cell dysfunction in pre-eclampsia. However, the mechanism of thrombocytopenia in this disorder does not appear to be related to alterations in the structure or biological function of vWF.